Michael Polanyi a rozwój idei porządku spontanicznego w XX wieku: w cieniu Hayeka - Leszek, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The idea of spontaneous order was crystallized — at least in the field of social science — as a result of considerations on how human communities are organized. The economic and philosophic thought of Friedrich von Hayek was of great importance to its development in the 20th century and nowadays many authors almost exclusively attribute to the Austrian scholar most of the achievements in this area. ‘Spontaneous order’ became a kind of Hayek’s trademark, carved out by him on the pages of Constitution of Liberty as well as Law, Legislation and Legislation and Liberty: Rules and Order and later promoted by dozens of monographs dedicated to him and his thought. Therefore — maybe a little in spite of the above-mentioned — in this article my aim is to briefly outline the appropriate topic of refl ections of Michael Polanyi, who seems to contribute to the idea as much as Hayek, but whose achievements in this field have not been fully recognized and studied yet, at least in Polish literature
Keywords: Polanyi, Michael (1891-1976); Hayek, Friedrich August von (1899-1992); spontaneous order